Psychoanalysis Ellie Chu Portrayed from Freud's and Maslow's Theories in "The Half of It" Movie - Ariyanti; Widyaningrum, Agnes (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
Psychology is the science that studies human behavior which is applied in analyzing human personality. This journal examines the application of the psychological theories of Sigmund Freud (Id, Ego, and Superego) and Abraham Maslow (physiological needs, safety needs, love and belonging needs, self-esteem, and self-actualization) in analyzing Ellie Chu the main character of the film "The Half of It". The author uses the descriptive qualitative research method to explain Ellie Chu's character. The author obtained data from watching the film "The Half of It" which was released by Netflix in 2020 and reading the script for the film "The Half of it". Directed by Alice Wu, this film follows the journey of Ellie Chu, a talented young writer who gets entangled in a journey of finding a complex identity in her small town. This analysis aims to show how the application of Freud's and Maslow's theories provides insight into Ellie's character development and motivation throughout the film. By exploring her subconscious desires and the fulfillment of her needs, we gain a deeper understanding of her actions, decisions, and emotional journey. Understanding the psychological underpinnings of Ellie's character increases our appreciation of the film's themes of identity, love, and self-discovery. It is hoped that from this analysis the readers can also be inspired by the story of Ellie Chu who can take responsibility for truth, honesty, and sacrifice.